A role for GATA factors in Xenopus gastrulation movements. - Fletcher, G; Jones, G; Patient, R; Snape, A (2006)
Gastrulation movements in Xenopus laevis are becoming increasingly well characterised, however the molecular mechanisms involved are less clear. Active migration of the leading edge mesendoderm across the fibronectin-coated blastocoel roof is necessary for further development of tissues such as head mesoderm, heart, blood and liver. The zinc finger transcription factors GATA4 and GATA6 are expressed in this migratory tissue during gastrulation, but their role here is unknown. This study further characterises the expression of GATA4 and 6 during gastrulation, and investigates their function in migratory behaviour. Gain-of-function experiments with these GATA factors induce cell spreading, polarisation and migration in non-motile presumptive ectoderm cells. Expression of a dominant-interfering form of GATA6, which inhibits transactivation of GATA targets, severely impairs the ability of dorsal leading edge mesendoderm to spread and translocate on fibronectin. Mosaic inhibition of GATA activity indicates that GATA factors function cell autonomously to induce cell spreading and movement in dorsal mesendoderm. Knockdown of specific GATA factors using anti-sense morpholinos indicates that GATA4 and GATA6 both contribute to dorsal mesendoderm migration in vitro. GATA4 and GATA6 are known to be involved in cell-specification of mesoderm and endoderm-derived tissues, but this is the first description of an additional role for these factors in cell migration.